The Information and Technology transfer in the context of Extensive Communication: the Babel.com (Información, cultura y sociedad, 2004)
The automation of the communication techniques gives relevance to extensive communication where the focus is not only on the information storage but also on the dispersion and universal use of the information. The vision brought about by the theory of systems reveals the extensive model and different information practices where the institutions and individuals develop a collective role, depending on a policy of information transfer. The information systems, consequently, act in a production line that control and appraise policies, objectives and goals possible by formal and informal structures mediation for the treatment and dissemination of the contents. In a traditional scientific communication model, that privileges the information storage, bookstores, publishers and traditional libraries are the principal mediators in the production, storage and dissemination of documents. In opposition, the extensive communication is a dynamic information system, in a scenario of interactive and multidimensional stocks, characterized by the insert of tools that promotes the interactivity, the hypertextuality and the hypermidiation.